2022
DOI: 10.1155/2022/2910782
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of Vitamin D on Respiratory Function and Immune Status for Patients with Chronic Obstructive Pulmonary Disease (COPD): A Systematic Review and Meta-Analysis

Abstract: Background. Many studies have demonstrated that vitamin D has clinical benefits when used to treat patients with chronic obstructive pulmonary disease (COPD). However, most of these studies have insufficient samples or inconsistent results. The aim of this meta-analysis was to evaluate the effects of vitamin D therapy in patients with COPD. Methods. We performed a comprehensive retrieval in the following electronic databases: PubMed, Embase, Cochrane Library, China National Knowledge Infrastructure (CNKI), Wan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…However, the specific molecular mechanism and functional relationship of aging in the occurrence and the development of chronic obstructive pulmonary disease and pulmonary fibrosis are not completely clear [ 49 ]. Finding these molecular mechanisms and functional relationships may bring hope to cure these diseases [ 50 ]. The present study showed that the effects of BGF did not have significant effects on the death rate, hypertension rate, and pneumonia in patients with COPD.…”
Section: Discussionmentioning
confidence: 99%
“…However, the specific molecular mechanism and functional relationship of aging in the occurrence and the development of chronic obstructive pulmonary disease and pulmonary fibrosis are not completely clear [ 49 ]. Finding these molecular mechanisms and functional relationships may bring hope to cure these diseases [ 50 ]. The present study showed that the effects of BGF did not have significant effects on the death rate, hypertension rate, and pneumonia in patients with COPD.…”
Section: Discussionmentioning
confidence: 99%
“…However, when the COPD RCTs were examined separately, there was no effect of vitamin D supplementation on acute respiratory infection, suggesting this finding likely driven by other patients [29]. A separate meta-analysis found a positive effect of vitamin D supplementation on the rate of COPD exacerbations (relative risk 0.40 95% CI 0.28–0.59, P < 0.00001) [30]. The discrepancies between these two meta-analyses may be explained by a wide variation of replacement strategies, with the latter analysis included studies with higher replacement doses.…”
Section: The Effects Of Vitamin D Deficiency and Treatment In Chronic...mentioning
confidence: 96%
“…Third, what is the optimum treatment regimen for VDD in COPD patients? The recent meta-analyses described earlier clearly show heterogeneity of doses, intervals, and routes of administration in clinical trial regimens [30]. This likely reflects the lack of consistency in the definitions and goals of various international consensus documents [42].…”
Section: Contributors Consequencesmentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%